Soy, glyphosate and human health. Some evidence in the Argentinian Dry Chaco Region (1990-2012) - Longhi, Fernando (2020)
In the last decades of the 20th century and the first decades of the 21st century, the Argentinian Dry Chaco Region (also known as Chaco Salteño or Umbral al Chaco), went through an intense process of deforestation associated with the advance of the agricultural frontier. The transgenic soybean-glyphosate agrotechnological package was the main protagonist of this process. In the broad ongoing debate pertaining to the effects of glyphosate on human health, epidemiological evidence on this relationship is not enough. That is why this article focuses on the use of mortality statistics, and therefore, its main contribution will be to make a first approach to the study of the epidemiological profile evolution of the region associated with the use of said package